Processos juntivos de causa : um estudo dos usos variáveis em textos escritos - Zago, Priscilla Zanforlim [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The goal here is to analyse the variable accomplishment of conjuctive processes of causa in the syntactic, semantic and pragmatic fields (as PAIVA, 1992; NEVES et al. 2008; PAIVA and BRAGA, 2010) and the possible correlation with the Discourse Traditions (as KABATEK, 2003; LONGHIN-THOMAZI, 2011a,b) in written texts by students in the Middle School of a public school in São José do Rio Preto, in the state of São Paulo. From a functional-based junction model (HALLIDAY, 1985; KORTMANN, 1997; RAIBLE, 2001; HOPPER e TRAUGOTT, 2003), we recognize that the casual mastery is realized through different structural combination modes between sentences and/or phrases and introduces semantic and pragmatic polysemy. We also understand that casualty involves logical implication as well as discursive-pragmatic factors, related to social aspects and individual intentions and expectations about the world. Therefore, the main goal of the research is achieved by an analyses of cause constructions consolidation that considers the intersection between the following options: i) tactical axis (parataxis, hypotaxis and subordination); ii) semantic axis (causa and effect, effect and causa, fact and explanation, assertion and explanation, and assertion and conclusion); and iii) pragmatic axis (content, epistemic and speech act – as SWEETSER, 1990). Then we investigate the extent to which discourse tradition, in which texts are used, helps to explain frequency and types os causally scheme found and, in the opposite direction, evaluate the extent to which causal junction schemes help to verge the discourse tradition. The corpus of this study consists of 130 texts of five writers, which were gathered from 2008 to 2011, under the University Extension Project “Development of workshops in reading, interpreting and writing” bound to UNESP, in São José do Rio Preto campus, and coordinated by teachers Luciani Tenani and Sanderléia Longhin. Regarding the ...

O objetivo deste trabalho é analisar a realização variável dos processos juntivos de causa nos domínios sintático, semântico e pragmático (cf. PAIVA, 1992; NEVES et al. 2008; PAIVA e BRAGA, 2010) e as possíveis correlações com as Tradições Discursivas (cf. KABATEK, 2006; LONGHIN-THOMAZI, 2011a,b) em textos escritos por alunos do segundo ciclo do Ensino Fundamental de uma escola pública de São José do Rio Preto/SP. A partir de um modelo funcionalista de junção (HALLIDAY, 1985; KORTMANN, 1997; RAIBLE, 2001; HOPPER e TRAUGOTT, 2003), reconhecemos que o domínio causal se concretiza por meio de diferentes modos estruturais de combinação entre orações e/ou sintagmas e apresenta polissemias semântica e pragmática. Entendemos, ainda, que a causalidade envolve implicação lógica e, também, fatores de ordem discursivo-pragmática, relacionados a aspectos sociais e a intenções e expectativas que os indivíduos têm no e do mundo. Nessa perspectiva, o objetivo maior desta pesquisa é concretizado pela consolidação da análise das construções de causa, considerando o cruzamento entre as opções: i) do eixo tático (parataxe, hipotaxe e subordinação); ii) do eixo semântico (causa/efeito, efeito/causa, fato/explicação, asserção/explicação e asserção/conclusão); e iii) do eixo pragmático (conteúdo, epistêmico e ato de fala – cf. Sweetser 1990). Investigamos, em seguida, em que medida a(s) tradição(ões) discursiva(s) em que os textos se inserem ajudam a explicar a frequência e os tipos de esquemas de causalidade encontrados. O corpus deste trabalho é composto por 130 textos de cinco escreventes coletados ao longo dos anos de 2008, 2009, 2010 e 2011, no âmbito do Projeto de Extensão Universitária “Desenvolvimento de oficinas de leitura, interpretação e produção textual” (PROEX) vinculado à UNESP, câmpus de São José do Rio Preto e coordenado pelas Profas. Luciani Tenani e Sanderléia Longhin ...
Keywords: Linguística; Análise linguística (Linguística); Gramática discursivo funcional; Causalidade; Língua portuguesa - Português escrito - São José do Rio Preto (SP); Linguistics; São Jose do Rio Preto (SP) - Ensino fundamental